Biomass production for sustainable aviation fuels: A regional case study in Queensland. (April 2015) - Murphy, Helen T.; O'Connell, Deborah A.; Raison, R. John; Warden, Andrew C.; Booth, Trevor H.; Herr, Alexander; Braid, Andrew L.; Crawford, Debbie F.; Hayward, Jennifer A.; Jovanovic, Tom; McIvor, John G.; O'Connor, Michael H.; et al.
Abstract: The aviation industry in Australia has aspirations to supply 5% of its domestic fuel use from biomass by 2020. The majority of available sources of biomass in Australia are lignocellulosic, and novel production systems that integrate existing land uses with energy production systems could have many benefits to growers and regions through enterprise diversification. This study assessed the operational and economic factors associated with lignocellulosic biomass supply for production of sustainable aviation fuel in a case study region in central Queensland, Australia. We examined the potential for biomass supply from native grasses, naturally regenerating woody vegetation (regrowth), and newly established plantings of short rotation trees (SRT) from the Fitzroy Catchment (14.2 million hectares). We outline a hypothetical industry scale-up strategy that achieves a production target of 470 ML of aviation fuel within a 25 year timeframe. We assess the amount of biomass required to support the scale-up strategy and the associated costs of supply to meet production targets during the scale-up. Approximately 5 million tonnes of biomass per year are required to support full production capacity after 25 years; 1.1 millions of land is required to be managed to supply this quantum of biomass. A preliminary assessment of the cost of supply for each feedstock indicates that grasses are most expensive at ~$142 t −1 due to relatively low biomass potentially available for harvest per hectare, and relatively high costs of harvesting and transporting compared with woody biomass. Regrowth is the least expensive at ~$56 t −1 due to low establishment and maintenance costs. We conclude that the case study region has the potential to produce sufficient biomass to support the hypothetical industry scale-up and that a mixed feedstock base maximises the sustainability of biomass supply. We discuss a range of sustainability issues associated with biomass production.